How Does Substitutional Doping Affect Visible Light Absorption in a Series of Homodisperse Ti11 Polyoxotitanate Nanoparticles?. Issue 32 (6th July 2015) - Chen, Yang; Jarzembska, Katarzyna N.; Trzop, Elżbieta; Zhang, Lei; Coppens, Philip
Abstract Homodisperse doped polyoxotitanate nanoclusters with formulae Ti11(MX)O14(OiPr)17 (M=Mn, Fe or Co; X=Cl, Br or I, OiPr=isopropoxide) display strongly dopant‐dependent properties. Spectroscopic solution and reflectance measurements backed up by density of states and time‐dependent DFT calculations based on the determined structures, show the prominent effect of FeX substitution by decreasing the HOMO–LUMO gap of the particles. The effect is attributed to the presence of an occupied Fe β orbital halfway up the bandgap, leading to long‐wavelength absorption with electron transfer to the titanium atoms of the cluster. Whereas the light absorption varies significantly with variation of the transition metal dopant, its dependency on the nature of the halogen atom or the change in dipole moment across the series is minor.